The Relationship Of Mother's Knowledge And Attitudes With Toddler's Growth And Development - Mutiara Btr, Anggina (Cattleya Darmaya Fortuna, 2022)
The quality of the next generation significantly relies on the growth and development of children, particularly in the crucial first three years of life when brain cell growth and neural network formation occur. Monitoring toddler growth and development is crucial for early detection of any developmental issues. This descriptive research with a cross-sectional approach aims to investigate the relationship between maternal knowledge, attitudes, and toddler growth and development in Hutapuli Village, Siabu District, Mandailing Natal Regency in 2023. The study population comprises mothers with toddlers in the village, with a total sample size of 33 participants selected using total sampling technique. Data collection involved primary and secondary sources, and data analysis utilized the chi-square test with a significance level of p<0.05. The findings indicate a significant relationship between maternal knowledge and attitudes and toddler growth and development (p = 0.003, p < 0.05). The study emphasizes the importance of mothers enhancing their knowledge and adopting positive attitudes towards supporting the optimal growth and development of toddlers. It is essential for mothers to actively engage in the growth and development process to ensure the overall well-being of their children and the future generation.